Gradient Trigger Mechanisms Related to Bistability Regimes in a Leech Heartbeat Model - Guan, Y.Zh; Liu, Sh.Q.; Zeng, Y.J. (Нейрофизиология, 2014)
We studied bursting patterns underlied by bifurcation phenomena and chaotic spiking in a computational leech heartbeat model. We observed the gradient physical properties of the ISI trains and amplitude (shift of the membrane potential) when the parameter gleak was mildly changed and found different bistable areas. The resulting computation implies that (i) classification of the intensity of the input information is feasible in this regime, (ii) a neuron’s working level can be marked by its range in a typical bifurcation, and (iii) there are invisible triggers underlying subtle mechanisms in the model. Ми досліджували пачкові імпульсні патерни, що формувалися на основі феноменів біфуркації, та хаотичну імпульсну активність у комп’ютерній моделі керування серцевими скороченнями у п’явки. Ми спостерігали градієнтність фізичних властивостей, що визначали характеристики послідовностей імпульсів та амплітуду (зміщення мембранного потенціалу), при невеликих змінах параметра gleak (провідності витоку). Було також виявилено, що існують різні зони бістабільності. Результати комп’ютерного моделювання вказують на те, що, по-перше, в такому режимі може забезпечуватися класифікація інтенсивності вхідної інформації; по-друге, робочий рівень для нейрона визначаеться його положенням у типовій біфуркації, і, по-третє, існують «невидимі» тригери, на яких базуються тонкі механізми моделі.